Level of Strategic Planning Needs of the Faculty of Arts and Sciences Members at Benghazi University - Ali Salim Maetoug, Salim (International Journal of Educational Research & Social Sciences, 2024)
This study aims to determine the level of strategic planning needs among faculty members at the faculty of Arts and Sciences Al-Abyar at Benghazi University. It aims to assertively identify any statistically significant differences in strategic planning needs based on gender, job title, and type of degree obtained. The study utilized descriptive research and employed a questionnaire as its primary instrument. The Cronbach's Alpha coefficient of 0.90 indicates high internal consistency. The study sample consisted of 61 members from the Faculty of Arts and Sciences, Al-Abyar, Benghazi University, representing 60% of the study population. The study's results indicate that the level of identification of planning needs among members in the Faculty is medium. Furthermore, there were no statistically significant differences in the level of strategic planning needs of faculty members attributable to gender. Also, there were no statistically significant differences in the level of strategic planning needs among faculty members regardless of their job title or type of degree. The challenges and issues facing Benghazi University strategic plan are complex and require a multifaceted and collaborative approach from all stakeholders, including the faculty members across all colleges and research centers.